Gender dysphoria: an overview - Capetillo Ventura, Nelly Cecilia; Jalil Pérez, Sarith Ileana; Motilla Negrete, Karla (UANL. Facultad de Medicina, 2015)
Gender dysphoria, gender identity disorder or transsexualism is a psychological condition that requires care and multiple health professionals; endocrinologists, surgeons and psychiatrists are just some of the professionals needed to address these situations. The following article is a summary of what transsexuality means, its history and treatment, as more and more people request our services with a therapeutic approach.